2009
DOI: 10.1123/jpah.6.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pedometer Use and Self-Regulation Strategies on Junior High School Physical Education Students’ Daily Step Counts

Abstract: Background:The aim of this study was to determine the impact of pedometer use and self-regulation strategies on adolescents’ daily physical activity.Methods:Junior high school students (n = 113) enrolled in seventh- and eighth-grade physical education classes (52 girls, 61 boys) volunteered to participate in a 5-week study to assess daily step counts. Ten physical education classes were randomly assigned to 1 of 3 groups: (a) self-regulation, (b) open, and (c) control.Results:A repeated-measures, mixed-model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…Viewing step counts was associated with more steps/day compared to a sealed control condition among a small number of young adolescents (Shimon and Petlichkoff, 2009) although this study did not use an objective measure to quantify PA. PA data were expressed as average counts per minute acting as adjustment for any differential wear time. Although the decline in accelerometer cpm over the four days of measurement is likely to be partly due to a drop in PA during weekends, the association remained when adjusted for weekday/weekend.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Viewing step counts was associated with more steps/day compared to a sealed control condition among a small number of young adolescents (Shimon and Petlichkoff, 2009) although this study did not use an objective measure to quantify PA. PA data were expressed as average counts per minute acting as adjustment for any differential wear time. Although the decline in accelerometer cpm over the four days of measurement is likely to be partly due to a drop in PA during weekends, the association remained when adjusted for weekday/weekend.…”
Section: Discussionmentioning
confidence: 94%
“…Graphing of step counts by young adolescents is associated with greater increases in step counts than when participants view (but do not graph) their step counts (Shimon and Petlichkoff, 2009). Research investigating the most effective way to utilise step count data to encourage behaviour change including refining different feedback methods and quantifying their effect on PA would be valuable (Watkinson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, studies have shown that action planning (forming concrete action plans) is associated with increased levels of exercise in both healthy and clinical populations (Brickell et al, 2006;Dombrowski & Luszczynska, 2009;Milne et al, 2002;. For instance, Shimon and Petlichkoff (2009) found that among seventh-and eighth-grade physical education students in a 5-week pedometer study, those in the action planning group produced 2071 to 4141 more steps than those in the control group. Similarly, prior studies revealed that coping planning (anticipating and coping with behaviour obstacles) contributes to the maintenance of regular exercise involvement Ziegelmann & Lippke, 2007).…”
mentioning
confidence: 96%
“…Arbour & Martin Ginis, 2009;Brickell, Chatzisarantis, & Pretty, 2006;Milne, Orbell, & Sheeran, 2002;Shimon & Petlichkoff, 2009). Nevertheless, whether or not the use of such types of exercise self-regulation can offset the negative impact of perceived stress on exercise behaviour remains obscure.…”
mentioning
confidence: 97%